Implementasi Mujahadah Nihadlul Mustaghfirin dalam Pembentukan Karakter pada Peserta Didik di SMA Islam Kandangan Kabupaten Temanggung - Safa'ah, Nur; Ifadah, Luluk; Azizah, Ana Sofiyatul (EDUCATIVA, 2023)
Education has a high level of significance, especially in terms of character education because education can optimize positive character content in the form of attitudes, noble morals, and tolerance. The objectives of this study are: (1) to know and analyze the implementation of mujahadah Nihadlul Mustaghfirin in character building in students (2) to know and analyze the implications of the implementation of mujahadah Nihadlul Mustaghfirin activities in character building in students (3) to know and analyze the supporting and inhibiting factors of the implementation of the mujahadah Nihadlul Mustaghfirin in character building in students at SMA Islam Kandangan Temanggung Regency. This research uses a phenomenological approach with a type of field research and uses qualitative research methods. Data sources use primary data and secondary data. Primary data include interviews and observations. While secondary data from the results of documentation. Furthermore, data collection techniques through observation with participatory observation types, interviews with semistructured interview types, and documentation. While data analysis techniques are in the form of data reduction, data presentation, and verification. The types of data triangulation used are data/source triangulation and method triangulation. The results showed (1) the implementation of mujahadah Nihadlul Mustaghfirin in character building for students at SMA Islam Kandangan was carried out using exemplary strategies, discipline, habituation, and creating a conducive atmosphere (2) the implications of the implementation of mujahadah Nihadlul Mustaghfirin activities on students at SMA Islam Kandangan formed 10 character education values as follows: religious, honest, tolerance, discipline, independent, hard work, responsible, caring for the environment, peace-loving, and communicative or friendly (3) Supporting factors for the implementation of mujahadah Nihadlul Mustaghfirin in character building in students at SMA Islam Kandangan include internal factors, namely from students. While external factors are support from teachers and fathers, support from parents, and adequate facilities and infrastructure. While the inhibiting factor is that there are still students who have a low level of awareness and lack of teacher enthusiasm for the implementation of mujahadah Nihadlul Mustaghfirin.